Quadratic Equation has Only Two Roots

We will discuss that a quadratic equation has only two roots or in other words we can say that a quadratic equation cannot have more than two roots.

We will prove this one-by-one.

A quadratic equation has only two roots.

Proof:

Let us, consider the quadratic equation of the general form

ax\(^{2}\) + bx + c = 0, (a ≠ 0) ............... (i)

Now divide each term by a (since, a ≠ 0), we get

x\(^{2}\) + \(\frac{b}{a}\)x + \(\frac{c}{a}\) = 0

⇒ x\(^{2}\) + 2 * x * \(\frac{b}{2a}\) + (\(\frac{b}{2a}\))\(^{2}\) – (\(\frac{b}{2a}\))\(^{2}\) + \(\frac{c}{a}\) = 0

⇒ (x + \(\frac{b}{2a}\))\(^{2}\) - \(\frac{b^{2} - 4ac}{4a^{2}}\) = 0

⇒ (x + \(\frac{b}{2a}\))\(^{2}\) – \((\frac{\sqrt{b^{2} - 4ac}}{2a})^{2}\) = 0

⇒ (x + \(\frac{b}{2a}\) + \(\frac{\sqrt{b^{2} - 4ac}}{2a}\))(x + \(\frac{b}{2a}\) - \(\frac{\sqrt{b^{2} - 4ac}}{2a}\)) = 0

⇒ [x - \((\frac{-b - \sqrt{b^{2} - 4ac}}{2a})\)][x - \((\frac{-b + \sqrt{b^{2} - 4ac}}{2a})\)] = 0

⇒ (x - α)(x - β) = 0, where α = \(\frac{- b - \sqrt{b^{2} - 4ac}}{2a}\) and β = \(\frac{- b + \sqrt{b^{2} - 4ac}}{2a}\)

Now we can clearly see that the equation ax\(^{2}\) + bx + c = 0 reduces to (x - α)(x - β) = 0 and the equation ax\(^{2}\) + bx + c = 0 is only satisfied by the values x = α and x = β.

Except α and β no other values of x satisfies the equation ax\(^{2}\) + bx + c = 0.

Hence, we can say that the equation ax\(^{2}\) + bx + c = 0 has two and only two roots.

Therefore, a quadratic equation has two and only two roots.


Solved example on quadratic equation:

Solve the quadratic equation x\(^{2}\) - 4x + 13 = 0

Solution:

The given quadratic equation is x\(^{2}\) - 4x + 13 = 0

Comparing the given equation with the general form of the quadratic equation ax\(^{2}\) + bx  + c = 0, we get

a = 1, b = -4 and c = 13

Therefore, x = \(\frac{- b ± \sqrt{b^{2} - 4ac}}{2a}\)

⇒ x = \(\frac{- (-4) ± \sqrt{(-4)^{2} - 4(1)(13)}}{2(1)}\)

⇒ x = \(\frac{4 ± \sqrt{16 - 52}}{2}\)

⇒ x = \(\frac{4 ± \sqrt{-36}}{2}\)

⇒ x = \(\frac{4 ± 6i}{2}\), [Since i = √-1]

⇒ x = 2 ± 3i

Hence, the given quadratic equation has two and only two roots.

The roots are 2 + 3i and 2 - 3i.





11 and 12 Grade Math 

From Quadratic Equation has Only Two Roots to HOME PAGE




Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.



New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.